Evaluation of Hyper-Heuristic Method Using Simple Random-Step Counting Hill Climbing in the Examination Timetabling Problem - Hamidan, Rusdi; Mukhlason, Ahmad (Institut Teknologi Sepuluh Nopember, 2020)
Exam Timetabling Problem (ETP) is a problem that occurs at the university. Solution to the ETP problem involves computational search methods to get results. In the process, if done manually it will require lot of time to achieve the optimal solution. ETP is basically allocating a schedule into room at particular time. Several previous researchers developed a hyper-heuristic method to obtain solutions that are expected to provide result that are close to optimal. In this study, ITC 2007 dataset will be used to find generic solutions that are near optimal. Simple Random (SR) was chosen as strategy to choose Low Level Heuristic (LLH) and Step Counting Hill Climbing (SCHC) was chosen as move-acceptance strategy for ETP. The results obtained show that one pair of algorithms proposed in this study is better than the literature while other algorithms also provide significant results.